2023
DOI: 10.3389/fbioe.2023.1096525
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic biodegradable polymer materials in the repair of tumor-associated bone defects

Abstract: The repair and reconstruction of bone defects and the inhibition of local tumor recurrence are two common problems in bone surgery. The rapid development of biomedicine, clinical medicine, and material science has promoted the research and development of synthetic degradable polymer anti-tumor bone repair materials. Compared with natural polymer materials, synthetic polymer materials have machinable mechanical properties, highly controllable degradation properties, and uniform structure, which has attracted mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 68 publications
0
11
0
Order By: Relevance
“…166 Consequently, the second generation of biomaterials emerged with the ability to undergo controlled degradation, possess ion exchange capacity, promote biomineralization, facilitate osteoinduction and hard tissue formation under physiological conditions, contributing to new bone formation. 167,168 However, these biomaterials lack the ability to interact with bone tissues through mutual or reciprocal ways in response to several physicochemical irritations, which is often criticized by clinical workers. The specific applications of the first-and secondgeneration biomaterials were illustrated in prior sections and will not be elaborated here.…”
Section: Physiotherapy Biomaterialsmentioning
confidence: 99%
“…166 Consequently, the second generation of biomaterials emerged with the ability to undergo controlled degradation, possess ion exchange capacity, promote biomineralization, facilitate osteoinduction and hard tissue formation under physiological conditions, contributing to new bone formation. 167,168 However, these biomaterials lack the ability to interact with bone tissues through mutual or reciprocal ways in response to several physicochemical irritations, which is often criticized by clinical workers. The specific applications of the first-and secondgeneration biomaterials were illustrated in prior sections and will not be elaborated here.…”
Section: Physiotherapy Biomaterialsmentioning
confidence: 99%
“…To overcome these drawbacks, natural polymers have been combined with other materials. (c) Synthetic polymers, including polystyrene, PLA, PGA, PCL, and polylactic-co-glycolic acid (PLGA), are often used, due to the possibility of regulating their mechanical properties, biodegradability, morphology, and structure during the fabrication process [64,65]. Recently, some in vitro studies have shown that 3D-printed PLA scaffolds are able to promote the adhesion, proliferation, and differentiation of osteoblast cells [66,67].…”
Section: Biomaterials For Bte Applicationsmentioning
confidence: 99%
“…Under these circumstances, stress conducts mainly along the plates and screws, resulting in a higher risk of screw breakage and fracture re-collapse. Some new types of bone substitutes have been reported in previous studies, such as hydrogel [ 3 ], gelatin, bioactive glass [ 4 ], and some synthetic polymer materials [ 5 ]. These innvative mateirals displayed good biocompatibility and osteoinductivity, but their elastic modulus was far different from that of bone, and they could not meet the needs of repairing irregular bone defects.…”
Section: Introductionmentioning
confidence: 99%